Influence of seasonal variation on in vitro fertilization success. - Michal Kirshenbaum; Alon Ben-David; Eran Zilberberg; Tal Elkan-Miller; Jigal Haas; Raoul Orvieto (PLoS ONE)
Objective To evaluate the influence of seasonal variation on in vitro fertilization (IVF) outcome in a large cohort population. Methods & materials A total of 5,765 IVF cycles conducted in Sheba medical center between 2013 and 2016 were retrospectively analyzed. The treatment cycles included 4214 ovarian stimulation and ovum pick up (OPU) cycles of which 3020 resulted in fresh embryo transfer and 1551 vitrified- warmed cycles of which1400 resulted in warmed embryo transfer. Cycles were assigned to seasons according to the date of OPU for fresh embryo transfer cycles or according to the date of embryo warming for vitrified warmed embryo transfer cycles. Results There were no statistically significant differences between the calendar months or seasons concerning the number of oocytes retrieved or fertilization rate in the fresh cycles. Throughout the 4 years of the study, the monthly clinical pregnancy rate fluctuated between 18.2% and 27.9% per fresh embryo transfer (mean 23.3%) and between 17.7% and 29.4% per vitrified warmed embryo transfer (mean 23%). These fluctuations did not follow any specific seasonal pattern. Conclusions Our study did not demonstrate any significant influence of the calendar months or seasons on the clinical pregnancy rates of fresh or vitrified warmed embryo transfers. It might be speculated that the complete pharmaceutical control of the ovarian and endometrial function, as well as the homogeneous treatments, procedures and laboratory equipment used during the study period have lowered the influence of seasonal effect on IVF treatment outcome.